Educational dispositives and formsof life (Nóema, 2016)
The pedagogical debate that has characterized recent years has often stressed the importance of the link between technological development and educational models. This relationship, however, too often emphasizes the ways in which the educational experience and training should be more carefully thought out, designed and set when viewed from the perspective of ‘good technological practices’. This value of the formative instance must start by taking a critical and in-depth reflection on implicit and explicit models that characterize the educational practices, enhancing the use and interpretation that the subjects make relevant. To allow this reflection is necessary to think of a pedagogical dispositive that does not lose sight of the complexity of the dimensions that act in connection with the ‘educational event’, and setting new paths of knowledge and new hypotheses of formation of self and others. Education interpreted in the light of the pedagogical dispositives can provide a valuable tool to imagine, design and evaluate the effects that every educational action produces related to the transformation of knowledge/knowing (savoir), life forms and forms of life.
Keywords: philosophy; pedagogy; dispositive